Occurrence patterns of coral-dwelling gall crabs (Cryptochiridae) over depth intervals in the Caribbean. - van Tienderen, K; van der Meij, S (PeerJ, 2016)
Coral-associated invertebrates form a major part of the diversity on reefs, but their distribution and occurrence patterns are virtually unstudied. For associated taxa data are lacking on their distribution across shelves and environmental gradients, but also over various depths. Off Curaçao we studied the prevalence and density of coral-dwelling gall crabs (Cryptochiridae), obligate symbionts of stony corals. Belt transects (10 × 0.5m(2)) were laid out at 6, 12 and 18 m depth intervals at 27 localities. Twenty-one known host coral species were surveyed, measured, and the number of crab dwellings was recorded to study the influence of host occurrence, depth distribution, and colony size on the occurrence rates of three Atlantic gall crab species: Opecarcinus hypostegus, Troglocarcinus corallicola and Kroppcarcinus siderastreicola. The overall gall crab prevalence rate was 20.3% across all available host corals at all depths. The agariciid-associated species O. hypostegus was found to mostly inhabit Agaricia lamarcki and its prevalence was highest at deeper depths, following the depth distribution of its host. Kroppcarcinus siderastreicola, associated with Siderastrea and Stephanocoenia, inhabited shallower depths despite higher host availability at deeper depths. The generalist species T. corallicola showed no clear host or depth specialisation. These results show that the primary factors affecting the distribution and occurrence rates over depth intervals differed between each of the three Atlantic cryptochirid species, which in turn influences their vulnerability to reef degradation.